PRIMARY SCHOOL TEACHERS’ SOFT SKILLS DEVELOPMENT WHILE TEACHING PHILOLOGICAL DISCIPLINES - Yu. Braiilko; O. Palekha; O. Rudych (Естетика і етика педагогічної дії)
The article is devoted to the topical issue of primary school teacher training in higher educational institutions. The purpose of the research is to investigate the process of developing primary school teachers’ soft skills in the process of teaching philological disciplines.